Behaviour of cyanidin-3-glucoside, β-lactoglobulin and polysaccharides nanoparticles in bulk and oil-in-water interfaces - Oliveira, Ana (2016)
Particle size distributions as well the interfacial and rheological properties of the films at the oil/water interface were used to study the effect of the interacting system between β-lactoglobulin, cyanidin-3-glucoside and pectin or chitosan in buffer solutions. The particles obtained were smaller with cy-3-gluc-β–lg-pectin and had reduced polydispersity with cy-3-gluc-β–lg-chitosan. Based on time dependent surface pressure results, β–lg-pectin mixtures showed a slower increase at the beginning of the measurement, while β-lg-chitosan mixtures showed no differences with β–lg alone. Contrarily, dilatational properties increased for ternary chitosan mixtures, but they remained similar to the pure protein in ternary pectin mixtures. Cy-3-gluc interfacial properties were reduced by the presence of pectin and chitosan. The interactions between cy-3-gluc and the biopolymers that have been selected in the present work resulted in a lower content of free polyphenol, reduced antioxidant properties as well as free β–lg. The impact of this effect was more relevant when pectin was used.